2017
DOI: 10.1002/adem.201700141
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Formation of Transition Aluminas from Boehmite

Abstract: Structural changes occurring during the conversion of boehmite over the transient phases g-, d-, and u-Al 2 O 3 to corundum were investigated. During the whole transition process, the specific surface area was reduced. The X-ray and electron diffraction experiments revealed that the transition from g-to u-Al 2 O 3 is continuous and that it proceeds over different d-states rather than over a distinct d-Al 2 O 3 phase. The reduction of the specific surface area was most pronounced prior to the onset of the phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…The progress of the continuous transition -Al 2 O 3 ! -Al 2 O 3 , the formation of several intermediate states between the metastable phases -Al 2 O 3 and -Al 2 O 3 , and the completed formation of -Al 2 O 3 at 975 o C were reported by Rudolph et al (2017).…”
Section: Phase Transition C-almentioning
confidence: 90%
See 2 more Smart Citations
“…The progress of the continuous transition -Al 2 O 3 ! -Al 2 O 3 , the formation of several intermediate states between the metastable phases -Al 2 O 3 and -Al 2 O 3 , and the completed formation of -Al 2 O 3 at 975 o C were reported by Rudolph et al (2017).…”
Section: Phase Transition C-almentioning
confidence: 90%
“…1). Their size varies between a few hundred nanometres and several micrometres (Rudolph et al, 2017). After annealing, this particle shape was preserved, but the corresponding crystallographic directions changed according to the orientation relationship ½010 boehmite k ½110 ð001Þ boehmite k ð001Þ :…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the previous published work, the tetrahedral site fraction was reported as 29% by Paglia et al (2003), or in the 31-34% range depending on processing temperature in another reference (Paglia et al, 2004). Rudolph et al (2017) found 45% Al fraction occupying tetrahedral sites. In fact, the Al 3+ cation location can be experimentally determined directly using 27 Al nuclear magnetic resonance (NMR) spectroscopy (Prins, 2020).…”
Section: Research Papersmentioning
confidence: 90%
“…Different distribution of vacancies over cation sites: one of the reasons why different structural descriptions of -Al 2 O 3 can be found in the literature for samples obtained by different technologies, with different crystallite sizes, etc. [13,14].…”
Section: Literature Reviewmentioning
confidence: 99%